Protein Quality, Haematological and Histopathological Studies of Rats Fed with Maize-based Complementary Diet Enriched with Fermented and Germinated Moringa Oleifera Seed Flour (2018)
This study is about the production of Maize-based complementary diet enriched with fermented and germinated moringa oleifera seed holds great promise in alleviating malnutrition so prominent among Nigerian children less than five years. However, there is scanty scientific information on its protein quality and safety which is necessary prelude to trials on human subjects. This study hence reports a controlled feeding trial involving 30 weanling wister rats housed in individual standard metabolic cages under room temperature condition. Following a subsequent daily feeding of the rats for 28 days, the protein quality of the diet with the haematological and histological studies was conducted. Results showed that the diets had a statistically significant effect on the growth rate on the test rats when compared with the control. The protein quality evaluation of the diets showed that the protein efficiency ratio ranged from 2.10 to 2.38 while the biological value ranged from 62.01 to 89.01 %. The true protein digestibility and protein rating were 55.79 to 79.25 % and 35.42 to 48.61 respectively. The relative weight of organs of the rats fed with the complementary diets showed that the weights of the kidney and liver ranged from 0.57 to 0.76g and 2.87 to 3.60g respectively. The growth performance of the rats fed with the formulated complementary diets showed that the formulated diets contributed to the growth status of the animals indicating that protein quality of the diets could support the growth and development of the infants. The haematological indices showed that the packed cell volume of the sample ranged from 36.67 to 40.67% and the red blood cell counts was 5.00 to 5.93 (×106 mm3). The white blood cell counts ranged from 3.47 to 3.98 (×103mm3) while the mean corpuscular haemoglobin and mean corspucularhaemoglobin concentration ranged from 10.04 to 11.71Pg and 33.10 to 33.45% respectively. Moreover, rat’s biopsy (histopathology) revealed no necrosis in the observed livers of the rats fed with the diets. Evidently, ogi-fermented moringa oleiefera seed complementary diet has no established detrimental effect and may therefore be safe for humans